2017
DOI: 10.1088/1741-4326/aa686c
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous neutron yield in indirect-drive inertial-confinement-fusion due to the formation of collisionless shocks in the corona

Abstract: Observations of anomalous neutron yield in the indirect-drive inertial confinement fusion implosion experiments conducted at SG-III prototype and SG-II upgrade laser facilities are interpreted. The anomalous mechanism results in a neutron yield which is 100-times higher than that predicted by 1D radiation-hydrodynamic simulations. 2D radiation-hydrodynamic simulations show that the supersonic, radially directed gold (Au) plasma jets arising from the laser-hohlraum interactions can collide with the carbon-deute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
1
12
1
Order By: Relevance
“…Similar situations can be found in the context of inertial confinement fusion (Zhang et al. 2017). While the medium considered here are spatially homogeneous, it would be worth studying how a shock transiting from one kind of medium to another, evolves.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Similar situations can be found in the context of inertial confinement fusion (Zhang et al. 2017). While the medium considered here are spatially homogeneous, it would be worth studying how a shock transiting from one kind of medium to another, evolves.…”
Section: Discussionsupporting
confidence: 72%
“…We leave a detailed study of the spectra expected under various conditions to future work. Similar situations can be found in the context of Inertial Confinement Fusion [55]. While the medium considered here are spatially homogeneous, it would be worth studying how a shock transiting from one kind of medium to another, evolves.…”
Section: Discussionmentioning
confidence: 52%
“…The beam-target reaction and thermonuclear reaction dominate in different stages and the peak neutron yield is 10 3 and 10 5 J −1 , respectively. Zhang et al (2017) observed anomalous neutron yield in indirect-drive ICF, and they attributed it to electrostatic shock wave collisions. Some of the deuterium particles are accelerated to high energy by the electrostatic shock wave and react with centre plasmas by means of the beam-target reaction (Zhang et al 2017;Shan et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2017) observed anomalous neutron yield in indirect-drive ICF, and they attributed it to electrostatic shock wave collisions. Some of the deuterium particles are accelerated to high energy by the electrostatic shock wave and react with centre plasmas by means of the beam-target reaction (Zhang et al 2017;Shan et al 2018). Other research such as that concerning laser-driven plasma collider (Fu et al 2015) also takes the beam-target reaction into account.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation